2021
DOI: 10.1002/cche.10467
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic extract from nejayote flour: Bioactive properties and its potential use as an antimicrobial agent of alginate‐based edible coatings

Abstract: The management of agri-food by-products or waste is considered a priority global industrial, economic, and environmental problem, and its solution requires a comprehensive and sustainable approach (García-García et al., 2017). The chemical composition of the residues that emerge is diverse and depends on the product nature and its processing. Inadequate disposal causes environmental problems, including greenhouse gas emissions, because of their high biodegradability, moisture, and microbial load (Fritsch et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
(57 reference statements)
0
3
1
Order By: Relevance
“…The alkaline conditions and nixtamalization temperature favor the leaching of phenolic compounds into the nejayote (TSP n ), where the highest concentration of TSP n was found, with values from 297.2 to 324.9 mg FAE L −1 , while in the washing water (TSP w ) values were from 179.8 to 230.0 mg FAE L −1 ( Table 5 ). These results were lower than those reported by other authors [ 24 , 40 ], possibly due to the type of maize and low TSP content in raw grain. In broth of FG without pedicel, (TSP b ) phenol contents were between 156.6 and209.3 mg FAE L −1 .…”
Section: Resultscontrasting
confidence: 92%
“…The alkaline conditions and nixtamalization temperature favor the leaching of phenolic compounds into the nejayote (TSP n ), where the highest concentration of TSP n was found, with values from 297.2 to 324.9 mg FAE L −1 , while in the washing water (TSP w ) values were from 179.8 to 230.0 mg FAE L −1 ( Table 5 ). These results were lower than those reported by other authors [ 24 , 40 ], possibly due to the type of maize and low TSP content in raw grain. In broth of FG without pedicel, (TSP b ) phenol contents were between 156.6 and209.3 mg FAE L −1 .…”
Section: Resultscontrasting
confidence: 92%
“…In other respects, nejayote and pericarp contain arabinoxylans, sugars, fibers, phenolic compounds, and calcium, which have the potential for value-added processing and utilization [5]. It was found that they have different uses, such as a culture medium for bacterial growth and for the production of bacteriocins [4], for animal feedstock [6], for the recovery of components with high added technological value (gelling capacity), and for use as bioactive compounds through their incorporation in food products and coatings [7,8]. Additionally, nejayote is a source of microorganisms, which shows its capability to generate high-value molecules from agro-industrial by-products [9].…”
Section: Introductionmentioning
confidence: 99%
“…The coatings have been formulated with various biopolymers, such as pectin [12], cellulose [13], bacterial cellulose [14], and other elements such as beeswax [10,11] nanocomposites [15], and rice starch [16]. Castañeda-Ruelas et al [8] studied a phenolic extract from nejayote flour applied on alginate-based edible coatings in order to evaluate its antimicrobial activity, and they found that the alginate-based coating with 2.3% nejayote phenolic extract showed total and low growth inhibition for Gram (+) and Gram (−) bacteria, respectively. Additionaly, Yoshida et al [17] extracted hemicelluloses from corn pericarp and formed a transparent film with mechanical strength and plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Total number and weight of tubers produced with irrigation wastewater from the corn cooking industry. In previous studies, it has been reported that nejayote contains a large amount of carbohydrates, calcium, phenolic compounds, and proteins such as albumins, globulins, and prolamines(Castañeda et al, 2021). Studies previous about wastewater content e show contain up to 76% carbohydrates, 10% protein, and 6% fat (Castañeda et al, 2021).…”
mentioning
confidence: 97%